In vitro responses of guinea pig peritoneal macrophages to Legionella pneumophila. - Kishimoto, R A (1981)
Transmission and scanning electron microscopy were used to study the phagocytosis of virulent and avirulent strains of Legionella pneumophila. The interaction between L. pneumophila and peritoneal macrophages from normal guinea pigs or from animals that had survived infection was studied. The virulent strains survived and proliferated within the phagocyte after ingestion by either type of macrophage, whereas the avirulent strain of bacteria was killed by normal macrophages. Although the addition of immune serum enhanced phagocytosis, the outcome was the same as with normal serum.